2017
DOI: 10.1038/s41598-017-15241-8
|View full text |Cite
|
Sign up to set email alerts
|

Breeding and study of two new photoperiod- and thermo-sensitive genic male sterile lines of polyploid rice (Oryza sativa L.)

Abstract: Male sterile lines play an important role in the utilization of heterosis. To explore and exploit the heterosis of polyploid hybrid rice, two photoperiod- and thermo-sensitive genic male sterile lines of polyploid rice, PS006 and PS012, were bred via chromosome doubling, complex hybridization and self-breeding. The characteristics of these two lines, including the agronomic traits, growth, development, fertility transformation and combining ability, were investigated. Both lines had good agronomic characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It is a mitogen disrupting agent which affects the microtubules that organize chromosomes in one side of the cell promoting symmetric cell division (reviewed in Alemanno and Guiderdoni, 1994). The induction of polyploidization in rice is generally performed through colchicine treatment in callus derived from anthers or seed cultures (Alemanno and Guiderdoni, 1994; Premvaranon et al, 2011; Zhang et al, 2017). In some cases, polyploidy induction causes genome rearrangements which can negatively affect seed production.…”
Section: Random Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a mitogen disrupting agent which affects the microtubules that organize chromosomes in one side of the cell promoting symmetric cell division (reviewed in Alemanno and Guiderdoni, 1994). The induction of polyploidization in rice is generally performed through colchicine treatment in callus derived from anthers or seed cultures (Alemanno and Guiderdoni, 1994; Premvaranon et al, 2011; Zhang et al, 2017). In some cases, polyploidy induction causes genome rearrangements which can negatively affect seed production.…”
Section: Random Mutationsmentioning
confidence: 99%
“…These lines showed high cross pollination ability, changes in fertility, and high combination ability. Hybrids obtained from these lines showed high heterosis and the potential to increase rice grain yield and quality (Zhang et al, 2017). The transcriptome of rice neo-tetraploids revealed a group of genes associated with fertility and heterosis.…”
Section: Random Mutationsmentioning
confidence: 99%
“…In addition, small RNA sequencing indicated that the partial sterilities of pollen and embryo sac were caused by specific differentially expressed miRNAs in autotetraploid rice (Li et al 2016 , 2017 ). Two photoperiod- and thermo-sensitive genic male sterile lines (PS006 and PS012) of polyploid rice were developed and their hybrids showed great heterosis and enormous potential for the improvement of rice quality and productivity (Zhang et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa L.) is one of the world's three major food crops. Faced with the pressure of a growing world population and the decrease in available arable land, it has become important to increase rice yield [4,117]. Now, this challenge becomes even greater owing to rapid climate changes, which has already become another immense threat to agriculture and food security.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some new autotetraploid hybrid rice combinations showing great yield potential have also been preliminarily bred. In their study of two-line male sterile line of polyploid rice, Zhang et al bred two photo-thermo-sensitive genic male sterile lines of polyploid rice for the first time, PS006 and PS012, through chromosome doubling, compound hybridization, and selfing [117]. The two male sterile lines had good flowering habits, high outcrossing rates, obvious changes in fertility, and good combining abilities.…”
Section: Polyploid Male Sterile Rice Linesmentioning
confidence: 99%